Cytomegalovirus pneumonia in an immunosuppressed sarcoidosis patient; a rare case of cytomegalovirus infection in a sarcoidosis patient - Mahnaz Mozdorian; Rozita khodashahi (Babol University of Medical Sciences, 2021)
Background: Sarcoidosis is a multisystemic granulomatosis disease that is mostly treated with immunosuppressive regimens. Studies demonstrated that these patients are prone to develop various infections. However, some infections including viral severe pneumonia is rare complications in sarcoidosis patients. In the present report, we described for cytomegalovirus (CMV) pneumonia in a female patient with sarcoidosis which has been successfully managed by ganciclovir. Case Presentation: Herein, we present a known case of sarcoidosis admitted to the emergency department because of fever, dyspnea, and productive cough. The patient was receiving prednisolone and methotrexate for months. The primary chest x-ray imaging revealed bilateral infiltration, especially in the upper lobes and hilar lymphadenopathy. The lung high resolution computed tomography showed a bilateral diffuse nodular pattern. After 72 hours of antimicrobial treatment, the fever was still present and the patient became a candidate for fiberoptic bronchoscopy. The gram staining of the bronchial fluid, polymerase chain reaction for tuberculosis, and PCP was also unremarkable. However, the PCR-CMV was positive. The quantitative PCR for CMV form blood sample was taken and the result came back as 3.6*103. With the impression of CMV pneumonia, a daily dose of 5mg of ganciclovir was prescribed. After 3 weeks of receiving 5mg/kg of ganciclovir twice daily (600mg daily), clinical symptoms, and dyspnea improved. Also, the radiological findings improved. Conclusion: In the present report, we demonstrated that sarcoidosis patients' receiving immunosuppressives are prone to develop CMV pneumonia, and fever and dyspnea were the alarm signs of CMV pneumonia is our patient which was successfully managed by ganciclovir.